2020
DOI: 10.48550/arxiv.2009.07932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Weak Flexibility in Planar Graphs

Abstract: Recently, Dvořák, Norin, and Postle introduced flexibility as an extension of list coloring on graphs [JGT 19']. In this new setting, each vertex v in some subset of V (G) has a request for a certain color r(v) in its list of colors L(v). The goal is to find an L coloring satisfying many, but not necessarily all, of the requests.The main studied question is whether there exists a universal constant ε > 0 such that any graph G in some graph class C satisfies at least ε proportion of the requests. More formally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Several papers [13,10,22,27,11,28] have explored (k, ǫ)-flexibility, with k ∈ {5, 4, 3}, of planar graphs with large enough girth or excluding certain cycles. A 'weak' notion of ǫ-flexibility where the domain of the request set is always the entire vertex set is studied in the context of planar graphs in [8,21].…”
Section: Flexible List Coloringsmentioning
confidence: 99%
“…Several papers [13,10,22,27,11,28] have explored (k, ǫ)-flexibility, with k ∈ {5, 4, 3}, of planar graphs with large enough girth or excluding certain cycles. A 'weak' notion of ǫ-flexibility where the domain of the request set is always the entire vertex set is studied in the context of planar graphs in [8,21].…”
Section: Flexible List Coloringsmentioning
confidence: 99%
“…It has been shown that there exists an ϵ > 0 such that every planar graph G is (6, ϵ)-flexible [14]. Several papers [9,11,12,14,22,23,28,29] have explored k ( , ϵ)-flexibility, with k {5, 4, 3} ∈ , of planar graphs with large enough girth or excluding certain cycles. A "weak" notion of ϵ-flexibility where the domain of the request set is always the entire vertex set is studied in the context of planar graphs in [9,22].…”
Section: Flexible List Coloringsmentioning
confidence: 99%
“…Apart from the original paper introducing flexibility [11], where some basic results in terms of maximum average degree were established, the main focus in flexibility research has been on planar graphs. In particular, for many subclasses G of planar graphs, there has been a vast effort to reduce the gap between the choosability of G and the list size needed for flexibility in G. As of now, some tight bounds on list sizes are known: namely, triangle-free 2 planar graphs [10], {C 4 , C 5 }-free planar graphs [21], and {K 4 , C 5 , C 6 , C 7 , B 5 }-free 3 planar graphs [17] are flexibly 4-choosable, and planar graphs of girth 6 [9] are flexibly 3-choosable. For other subclasses G of planar graphs, an upper bound is known for the list size k required for G to be flexibly k-choosable [7,19].…”
Section: :3mentioning
confidence: 99%
“…5 -free 3 planar graphs [17] are flexibly 4-choosable, and planar graphs of girth 6 [9] are flexibly 3-choosable. For other subclasses  of planar graphs, an upper bound is known for the list size k required for  to be flexibly k-choosable [7,19].…”
Section: Introductionmentioning
confidence: 99%